2014
DOI: 10.1111/pbr.12223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of VRN‐1 and PPD‐D1 genes on heading time in European bread wheat cultivars

Abstract: The variation of the vernalization (VRN-1) and photoperiod (PPD-1) genes offers opportunities to adjust heading time and to maximize yield in crop species. The effect of these genes on heading time was studied based on a set of 245 predominantly spring cultivars of bread wheat from the main eco-geographical regions of Europe. The genotypes were screened using previously published diagnostic molecular markers for detecting the dominant or recessive alleles of the major VRN-1 loci such as: VRN-A1, VRN-B1, VRN-D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
3
34
0
2
Order By: Relevance
“…† LT 50 with other traits correlated within 12 cultivars: Antonivka, Kniahynia Olha, Ekspromt, Alma DS, Epokha odeska, Nordika, Kena DS, Raduza, Dagmar, Effect, Quebon, Simano. difference between allelic groups under field conditions in the UK. Molecular genetic studies of Ppd-D1 alleles showed higher occurrence of the photoperiod insensitive Ppd-D1a allele in the southern regions, while the photoperiod sensitive allele Ppd-D1b predominates western and northern regions of Europe (Šíp et al 2011;Kiss et al 2014;Shcherban et al 2015). The current study confirms previous reports that expression of earliness is mainly determined by the polymorphism of Ppd-D1 alleles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…† LT 50 with other traits correlated within 12 cultivars: Antonivka, Kniahynia Olha, Ekspromt, Alma DS, Epokha odeska, Nordika, Kena DS, Raduza, Dagmar, Effect, Quebon, Simano. difference between allelic groups under field conditions in the UK. Molecular genetic studies of Ppd-D1 alleles showed higher occurrence of the photoperiod insensitive Ppd-D1a allele in the southern regions, while the photoperiod sensitive allele Ppd-D1b predominates western and northern regions of Europe (Šíp et al 2011;Kiss et al 2014;Shcherban et al 2015). The current study confirms previous reports that expression of earliness is mainly determined by the polymorphism of Ppd-D1 alleles.…”
Section: Discussionsupporting
confidence: 90%
“…To meet this challenge, the genetic yield potential should be enhanced and the gap between actual and potential yield should be minimized. Target manipulation of the genetic systems responsible for the wheat adaptation to specific local environments will be crucial to maximize wheat grain yield (Gomez et al 2014;Shcherban et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers are widely used for the assessment of the genetic diversity of bread wheat and its related species on the genomic level [2,3,23,26] as well for the estimation of allelic variation of the particular genes in collections [29,34,44,65]. The information of allele distribution and genetic diversity is of great importance for the development of marker-assisted wheat breeding strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is chromosome 2D where the genes for adaptability to the environment, such as the Ppd-D1 gene for the response to photoperiod, Rht-8c for dwarfism, etc. are located [31][32][33][34][35]. Moreover, chromosome 2D harbors the FRIZZY PANICLE gene responsible for the number of spikelets formation (among homologues of most importance) [36], C gene, which determines the compact spike [37], Iw2 gene, which controls the absence of glaucousness on vegetative and generative organs of plant [38,39], Pis1 gene, which controls a multi-gynoecium (synonym: three pistils) [40], QTLs of 1000 grain weight [41] (D1 and D4 conferring hybrid dwarfism [42,43] and other genes.…”
Section: Competing Interests: No Authors Have Competing Interestsmentioning
confidence: 99%
“…С использованием аллель-специфичных маркеров у тритикале были обнаружены доминантные аллели Vrn-A1a, Vrn-B1a, Vrn-B1b, Vrn-B1c (58,59), ранее выявленные у мягкой пшеницы (48,(60)(61)(62)(63).…”
unclassified